COVID-19 vaccination hesitancy and associated factors among solid organ transplant recipients in China - Tingting Chen; Xiaoyu Li; Qiuting Li; Lihong Huang; Qingqing Cai; Yuzhu Wang; Ying Jiang; Qing Xu; Qianzhou Lv; Jina Wang (Taylor & Francis Group, 2021)
The mortality rate from COVID-19 appears to be higher in solid organ transplant (SOT) recipients when compared with other populations. Vaccination is a key strategy to prevent the COVID-19 pandemic. However, it is unclear how readily SOT recipients will get vaccinated against COVID-19. We conducted an internet-based survey to investigate the vaccination willingness among Chinese SOT recipients and further explore possible influencing factors. Eight hundred and thirteen respondents participated in the survey. Overall, 46 (5.7%) recipients were vaccinated against COVID-19, while 767 (94.3%) were not. Among those not vaccinated, 175 (22.8%) intended to be vaccinated, while 592 (77.2%) were categorized as vaccine-hesitant. The most common reason for vaccination hesitancy is fear of preexisting comorbidities, followed by fear of side effects and doctors' negative advice. Factors associated with vaccination willingness were as follows: with liver transplantation, the main source of information on COVID-19 vaccines was from medical doctors, scientists, and scientific journals, with at least college-level education, positive intention toward influenza vaccination during the current season, perceived importance of vaccination for SOT recipients, and having been vaccinated against influenza during the last season. Our survey indicated the necessity for SOT recipients to receive more comprehensive and accessible health education about vaccination and emphasized the critical role of transplantation physicians in promoting vaccine acceptance among SOT recipients. We hope that our survey results will help governments to better target communication in the ongoing COVID-19 vaccination campaign.